The analysis of financial performance: the case study for Scope International (M) Sdn Bhd / Mohd Ridhwan Kamal - Kamal, Mohd Ridhwan (Faculty of Business and Management, 2009)
This study reveals the analysis of financial performance for Scope International (M) Sdn Bhd from year 2004 to year 2008. Scope International (Standard Chartered operation are wholly owned subsidiary by Standard Chartered Bank. August 2002, Scope International (M) Sdn Bhd was established to design, develop, and implement to support wholesale banking operation of scb. the objectives the studies are to investigate which year is more profitable for the company and to identify the flow of the performance by the company during the year studied. to analyze this company’s financial performance, financial ratios and common-size analysis were used and calculated based on the information disclosed on the financial statement of the companies. the study identifies the financial strength on certain criteria. five types of ratios were selected and constructed. each ratios represents the major categories namely liquidity, profitability, operating, asset utilization, and leverage ratio. an analysis has been given on each of the selected ratios after been calculated, the purpose is to analyze which year studied can be make profit (favorable) or not. The same way goes to common-size analysis, where the way these company managing their assets, liability, and equity from year 2004 to 2008 were fully analyzed. the results show that this company was doing well in managing their financial activities in the recent years. in summary, this study concludes the year give more profitable is in 2007 and Scope International (M) Sdn Bhd are improving from year to year which show their financial performance are better compare to their previous year even though when the global economy are being hit by the financial turmoil, Scope International (M) Sdn Bhd still can manage and strengthen their financial very well.